Hubungan antara Ketergantungan Nikotin berdasarkan Fagerstrom Test for Nicotine Dependence (FTND )dengan Gangguan Fungsi Kognitif yang Dinilai dengan MoCA-Ina - Ida Ratna Nurhidayati; Eka Syafnita (Majalah Sainstekes, 2018)
The aim of the study to know correlation between nicotine dependencybased on Fragerstom Test for Nicotine Dependence (FTND) and cognitive impairment that being assessed by MoCA-Ina. This is a cross sectional study was carried out in YARSI University. Consecutive sampling was used as the sampling method taken form academic community as the population. Data was analyzed using Chi-square. Forty-four subjects were enrolled in this study. All of them were being assessed using (FTND) and Montreal Cognitive Assessment Indonesian Version (MoCA-Ina). Thirty subjects were found having cognitiveimpairment with p value 0.045, there is a correlation between nicotine dependency based on FTND and cognitive impairment that being assessed by MoCA-Ina; correspond with receptor disinvitation theory. The result of study can be used by physician in counselling and early detection of cognitive impairment because the number of smokers in Indonesia is still high.